Building a measure of social responsibility in light of the crises facing society for students of the University of Mosul - the humanities departments (Eurasian Journal of Humanities and Social Sciences, 2022)
The research aims to build a scale of social responsibility among students of the University of Mosul - the humanities departments - in the College of Education, and for the purpose of achieving this, the researchers reviewed the literature and studies and in the light of it prepared the scale of social responsibility according to four main areas (the scale of personal social responsibility, moral social responsibility, responsibility National Social, the Social Responsibility of the State) and after preparing the paragraphs of the scale according to the fields, it was presented to a group of experts, and the scale had the approval of all of them. The sample was chosen randomly from students of the humanities departments - College of Education - and the researchers extracted the validity and psychometric properties of the scale, as well as finding stability, and the scale became composed of (44) items, thus achieving the goal of preparing a scale of social responsibility